The role of tungsten species in the transition of anodic nanopores to nanotubes formed on iron alloyed with tungsten. (20th June 2019) - Fadillah, Laras; Takase, Kentaro; Kobayashi, Hikaru; Turczyniak-Surdacka, Sylwia; Strawski, Marcin; Kowalski, Damian; Zhu, Chunyu; Aoki, Yoshitaka; Habazaki, Hiroki
Abstract: The effect of alloying of sputter-deposited Fe with 9 at.% tungsten on the growth of nanoporous anodic oxide was studied in ethylene glycol electrolyte containing 0.1 mol dm −3 ammonium fluoride and 1.5 mol dm −3 water. The classic nanoporous anodic film (Al2 O3 -like) was developed on pure Fe while the transition of nanopores to nanotubes (TiO2 -like) was observed for anodizing of Fe-W alloy. The pores/nanotubes having average diameter 50–110 nm and 30–60 nm on pure Fe and Fe-W alloy anodized at voltage 40–60 V, respectively. Both nanoporous/nanotubular anodic films grow in line with the field assisted flow model with a few fundamental details: i) transition of nanopores to nanotubes is observed upon anodizing of Fe-W alloy, ii) significant reduction of the cell size (nanotube diameter) is obtained on Fe-W alloy, iii) relatively thick layer is produced at Fe-W alloy/oxide interface. The primary reason of this transition to nanotubes as well as chemical changes is discussed in view of effective modification of the cell boundary region with tungsten species, probably WF6 compound, upon growth of anodic film under influence of high electric field strength. The possible reason of developing the space in between nanotubes is faster kinetics of WF6 reaction with water over the presence of low solubility FeFx species. Alloying of iron is one of the effective ways to modify the nanostructure of the anodic film on iron. Graphical abstract: Image 1 Highlights: Anodizing of Fe with addition of 9 at.% of W results in transition of nanoporous oxide into nanotubular structure. Anodic nanotubes formed on Fe-W alloy composed of Fex Oy and WO3 domains grow in line with the field assisted flow model. Faster kinetics of WF6 decomposition over the presence of low solubility FeFx is observed.